2018
DOI: 10.1111/pai.12881
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of repeated infections in asthma persistence from preschool to school age: Design and characteristics of the PreDicta cohort

Abstract: The PreDicta cohort presented no differences in non-asthma related measures; however, it is well balanced regarding key phenotypic characteristics representative of "preschool asthma".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 37 publications
1
41
0
Order By: Relevance
“…We processed nasopharyngeal samples (NPS) obtained from a subgroup of children with asthma and healthy controls recruited in the PreDicta cohort 27 Figure 1A). We observed that 87.5% (7 out of 8) of these vMAGs were identified in healthy samples compared to 37.5% (3 out of 8) in asthma ( Figure 1A), along with an elevated number of sequencing reads mapping to them ( Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We processed nasopharyngeal samples (NPS) obtained from a subgroup of children with asthma and healthy controls recruited in the PreDicta cohort 27 Figure 1A). We observed that 87.5% (7 out of 8) of these vMAGs were identified in healthy samples compared to 37.5% (3 out of 8) in asthma ( Figure 1A), along with an elevated number of sequencing reads mapping to them ( Figure 1B).…”
Section: Resultsmentioning
confidence: 99%
“…This is also the case for different asthma phenotypes and severity levels. Nevertheless, the PreDicta cohort was shown to be representative of preschool asthma 27 . Finally, the identified viromes and bacteriomes refer to the specific tissue niche of the nasopharynx and further investigation is needed to study viral presence along the respiratory tract.…”
Section: Dysbiotic Structure Of the Asthmatic Viromementioning
confidence: 99%
See 2 more Smart Citations
“…Readers with a special interest in asthma will also read with interest articles on the role of pathogens either for the contribution of exacerbations, prevention by active innate immune stimulation with bacterial compounds and a meta‐analysis of early fish consumption and the diagnosis of asthma later in life …”
mentioning
confidence: 99%